Kipo Moti: Nonverbal Communication of Mee Ethnic in Papua - Mahmud, Adi F.; Dollah, Syarifuddin (STAIN Majene, 2024)
Nonverbal communication has a vital role in social interaction. The majority of communication in social life involves nonverbal language. This research aims to (1) explore in depth Kipo Moti as the nonverbal communication of the Mee tribe in Papua and (2) discover the context of the use of Kipo Moti as the nonverbal communication of the Mee tribes in Papua. Research uses a qualitative approach with a descriptive design. A total of one subject was selected using the purposive technique with particular consideration. Open-ended questions are used in in-depth interviews and document analysis from online sources. Three sections made up the interview: The first section of the interview concentrated on the overall characteristics of the Mee tribe in Papua; the second section focused on the culture of the Kipo Moti, which is the nonverbal language of the Mee tribe; and the third section focused more on the Kipo Moti use as a nonverbal tongue in various contexts. The interview transcript results are analyzed using three phases that are taken from Gay et al. (2009). first reading/memorization, describing, and classifying. Research results show that Kipo Moti for the Papua Mee tribe is a form of nonverbal communication that expresses feelings of appreciation, love, respect, and pride toward one another or others. Furthermore, the Kipo Moti language can be used in a variety of situations to indicate three symbols; First. A symbol of friendship. Second. A symbol of peace. Third. A symbol of agreement.